The Role of Empowering Leadership in Facing the Era of the Digital Industrial Revolution: Literature Review - Widyo, Dandri; Indrajaya, Muhammad Galih; Ratnawati, Intan (Research Horizon, 2024)
This research aims to explore the role of empowering leadership in facing the era of digital revolution/industry 4.0. The problem raised is the low performance of employees in several organizations caused by a lack of autonomy, trust, and support from leaders in the era of the digital revolution. The dynamic increase in the application of Industry 4.0 technology makes the orientation of organizations towards dehumanization result in a lot of employee concerns on technology which can lead to a loss of view of the centrality of human resources, because organizationrequires employees who are adaptive in the influence of employee motivation and work engagement. To overcome this, this study examines how empowering leadership can increase the behavior of extra employee roles which leads to improved performance in the era of the industrial revolution. The method used in this study is literature review. Research findings show that empowering leadership significantly improves employee performance. Employees who are given more autonomy and support by leaders can show proactive behavior that ultimately increases productivity and quality of work. The contribution of this study is to provide empirical evidence that leadership empowerment can be an effective strategy in improving employee performance in organizations. These findings are relevant for leaders who want to create a more collaborative and productive work environment in the era of the digital/Industry 4.0 revolution.